Applications of Nanotechnology in Sensor-Based Detection of Foodborne Pathogens - Kumar, Harsh; Kuča, Kamil; Bhatia, Shashi Kant; Saini, Kritika; Kaushal, Ankur; Verma, Rachna; Bhalla, Tek Chand; Kumar, Dinesh (Sensors (Basel, Switzerland), 2020)
The intake of microbial-contaminated food poses severe health issues due to the outbreaks of stern food-borne diseases. Therefore, there is a need for precise detection and identification of pathogenic microbes and toxins in food to prevent these concerns. Thus, understanding the concept of biosensing has enabled researchers to develop nanobiosensors with different nanomaterials and composites to improve the sensitivity as well as the specificity of pathogen detection. The application of nanomaterials has enabled researchers to use advanced technologies in biosensors for the transfer of signals to enhance their efficiency and sensitivity. Nanomaterials like carbon nanotubes, magnetic and gold, dendrimers, graphene nanomaterials and quantum dots are predominantly used for developing biosensors with improved specificity and sensitivity of detection due to their exclusive chemical, magnetic, mechanical, optical and physical properties. All nanoparticles and new composites used in biosensors need to be classified and categorized for their enhanced performance, quick detection, and unobtrusive and effective use in foodborne analysis. Hence, this review intends to summarize the different sensing methods used in foodborne pathogen detection, their design, working principle and advances in sensing systems.
Keywords: nanotechnology; biosenzitivní techniky; Bacteria; Nanoparticles; safety; Foodborne Diseases; grafit; nanotechnologie; nanostruktury; Biosensing Techniques; Nanostructures; Nanotechnology; Graphite; nanotrubičky uhlíkové; sensor; Humans; foodborne pathogens; nanočástice; Nanotubes, Carbon; nemoci přenášené potravou; nanomaterials; lidé